The cancer-retina antigen recoverin as a potential biomarker for renal tumors - Golovastova, Marina O.; Bazhin, Alexandr V. (Tumor biology, 2016)
The renal cell carcinoma is the ninth most common cancer with an increasing occurrence and mortality. Recoverin is the first retina-specific photoreceptor protein that was shown to undergo aberrant expression, due to its promoter demethylation, as a cancer-retina antigen in a number of malignant tumors. In this work, we demonstrated that recoverin is indeed expressed in 68.4 % of patients with different subtypes of renal cell carcinoma, and this expression has tendency to correlate with tumor size. Interestingly, 91.7 % of patients with the benign renal tumor, oncocytoma, express recoverin as well in their tumor. Epigenetic analysis of the recoverin gene promoter revealed a stable mosaic methylation pattern with the predominance of the methylated state, with the exception of -80 and 56 CpG dinucleotides (CpGs). While the recoverin expression does not correlate withoverall survival of the tumor patients, the methylation of the recoverin gene promoter at -80 position is associated with better overall survival of the patients. This work is the first report pointing towards the association of overall survival of renal cell carcinoma (RCC) patients with promoter methylation of a cancer-retina antigen. Taken together, these data allow to consider recoverin as a potential therapeutic target and/or marker for renal tumors.
Gesehen am 11.03.2020